Response surface methodology optimization of electrode modification parameters toward hydrazine electrooxidation on Pd/MWCNT/GCE - Berdan Ulaş (MANAS: Journal of Engineering, 2023)
In this study, MWCNT supported Pd (Pd/MWCNT) was synthesized by NaBH4 reduction method as catalyst for hydrazine electrooxidation reaction (HEOR). Characterization methods namely inductively coupled plasma mass spectrometry (ICP-MS), elemental mapping, and scanning electron microscopy with energy dispersive X-ray (SEM-EDX) were used to analyze the surface morphology and metal composition of the catalysts. The Pd/MWCNT catalyst's average particle size is estimated to be 6.35 nm based on SEM images. Glassy carbon electrode (GCE) modification parameters namely the amount of catalyst ink transferred to the GCE surface (Vs), ultrasonication time of the catalyst ink (tu), and the drying time of the Pd/MWCNT/GCE (td) were optimized by using response surface methodology as 4.92 μL, 1 min and 19.52 min, respectively. Experimental specific activity value for HEOR was obtained as 7.13 mA cm-2 with 2.59% deviation under optimum conditions. Optimization of electrode preparation conditions is an inexpensive and facile method that could be used to improve the performance of anode catalysts for fuel cells.